Migration Studies and Academic Research on International Migration Policies in Argentina - Domenech, Eduardo (2017)
This article approaches the historical development of the field of migratory studies in Argentina and makes a review of the academic production around the so - called "migratory policies." The systematization of these studies, historically placed on migration policies, aims to highlight some of the most significant contributions of the research during the last 30 years, to understand or explain various aspects and dimensions of the Argentinean migration policy. To achieve this, texts were selected that derived from empirical research that explicitly assume the migratory policies as the object of study, or whose themes and research problems adopt as a framework for discussion the policies and practices aimed at regulating migration and mobility in Argentina. The organization and presentation of these selected texts consider issues related to the interests and thematic concerns, disciplinary and analytical approaches, distinct periods, scales of analysis and sources of information.